Application Of Criminal Law Against Perpetrators Of Sexual Violence In Children - Theo Sifra AHASIA; I Nyoman NURJAYA; Milda ISTIQOMAH (International Journal of Environmental, Sustainability, and Social Science, 2021)
Children are the nation's assets and the next generation's state. Every child has the same human rights as humans in general, as is constantly reported in the mass media about cases of child sexual abuse that need to get an important spotlight for the law to act as soon as possible. Criminal penalties for perpetrators of sexual violence as stated in the Criminal Code and the Child Protection Act are considered ineffective, so the Government passed PERPU No. 1/2016 into UU 17/2016, which applies punishment for perpetrators of sexual violence crimes, including by chemically imposing castration. Arrangements on child sexual intercourse are also regulated in Child Protection Act No.35 of 2014. About the criminal acts of sexual violence against children in articles 76D, 76E and in KUHP, several articles protect children against sexual violence; protection of children is indicated by the provision of criminal punishments for perpetrators. Sexual violence crimes in Indonesia are increasing every year.